2020
DOI: 10.1021/acs.jnatprod.0c00535
|View full text |Cite
|
Sign up to set email alerts
|

Staprexanthones, Xanthone-Type Stimulators of Pancreatic β-Cell Proliferation from a Mangrove Endophytic Fungus

Abstract: This project was focused on the discovery of novel compounds that promote endogenous β-cell regeneration. Screening of extracts identified the fungus Stachybotrys chartarum as a promising candidate. After fermentation and extraction of S. chartarum, we isolated five new prenylated xanthones, namely, staprexanthones A–E (1–5), with staprexanthone A (1) being the first natural xanthone bearing a rare 4,5-dimethyl-1,3-dioxolane moiety. Compounds 1, 2, and 5 significantly increased β-cell numbers in vivo in a zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…335 A series of 17 new prenylated shikimate derivatives pestalotheols I-Q 845-853 and cytosporins O-W, 854-861 were isolated from Pseudopestalotiopsis thea, 336 while prenylated xanthones staprexanthones A-E 862-866 were reported from Stachybotrys chartarum. 337 Three of the compounds (862, 863 and 866) were zebrash pancreatic b-cell promoters at 10 mM. Trichoderma longibrachiatum isolated from the roots of the halophyte Suaeda glauca was the source of the weakly antifungal, tricyclic sesquiterpenoid trichodermene A 867.…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
“…335 A series of 17 new prenylated shikimate derivatives pestalotheols I-Q 845-853 and cytosporins O-W, 854-861 were isolated from Pseudopestalotiopsis thea, 336 while prenylated xanthones staprexanthones A-E 862-866 were reported from Stachybotrys chartarum. 337 Three of the compounds (862, 863 and 866) were zebrash pancreatic b-cell promoters at 10 mM. Trichoderma longibrachiatum isolated from the roots of the halophyte Suaeda glauca was the source of the weakly antifungal, tricyclic sesquiterpenoid trichodermene A 867.…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
“…By comparing the size and fluorescence intensity of liver tumors, we found that compounds 1 and 2 can inhibit liver hyperplasia of zebrafish larvae at a concentration of 10 μmol/L (Figs. 2A, B, 3), which suggests that they are promising lead compounds for a new antihepatoma drug (Gan et al 2020). However, the esterification products of 1 (i.e., 3 and 4) showed no activity (Figs.…”
Section: Resultsmentioning
confidence: 97%
“…100 A Setophoma strain yielded a xanthone monomer 547 and three dimers 548–550 , 87 whilst Stachybotrys strain produced five new prenylated xanthones, staprexanthones A–E ( 551–555 ) with 551 being the first natural xanthone bearing a rare 4,5-dimethyl-1,3-dioxolane moiety as stimulators of pancreatic β-cell proliferation. 246 From the Chinese mangrove endophytes, a xanthone dimer 556 and its related chromanone dimers 557 and 558 were isolated. 147 A Peniophora strain produced six new xanthone derivatives 559–564 , including the cytotoxic incarxanthone B ( 560 ) with thiol group and the xanthone dimer incarxanthone F ( 564 ) with a C3-N-C2′bridge.…”
Section: Secondary Metabolites From Mangrove Fungimentioning
confidence: 99%
“…143,144 From endophytic fungus Nectria sp. HN001, nectriacids A-C (246)(247)(248), three new fatty acids were isolated, and 247 and 248 were found to show inhibitory activity against a-glucosidase with IC 50 values of 23.5 and 42.3 mM, respectively. 78 Two new succinic acid derivatives, xylacinic acids A (249) and B (250), were isolated from the mangrove-derived fungus Xylaria cubensis PSU-MA34.…”
Section: Reviewmentioning
confidence: 99%